Study of cost functions in three term backpropagation for classification problems [electronic resource] - 409910 Puspadevi Kuppusamy; Siti Mariyam Shamsuddin, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Sains Komputer) ) - Universiti Teknologi Malaysia, 2008